Identification of second-generation P2X3 antagonists for treatment of pain. Issue 8 (1st May 2018) - Ginnetti, Anthony T.; Paone, Daniel V.; Stauffer, Shaun R.; Potteiger, Craig M.; Shaw, Anthony W.; Deng, James; Mulhearn, James J.; Nguyen, Diem N.; Segerdell, Carolyn; Anquandah, Juliana; Calamari, Amy; Cheng, Gong; et al.
Graphical abstract: A second-generation small molecule P2X3 receptor antagonist has been developed. The lead optimization strategy to address shortcomings of the first-generation preclinical lead compound is described herein. These studies were directed towards the identification and amelioration of preclinical hepatobiliary findings, reducing potential for drug-drug interactions, and decreasing the projected human dose of the first-generation lead. Abstract: A second-generation small molecule P2X3 receptor antagonist has been developed. The lead optimization strategy to address shortcomings of the first-generation preclinical lead compound is described herein. These studies were directed towards the identification and amelioration of preclinical hepatobiliary findings, reducing potential for drug-drug interactions, and decreasing the projected human dose of the first-generation lead.